2021
DOI: 10.1108/ijilt-03-2021-0046
|View full text |Cite
|
Sign up to set email alerts
|

Exploring user experience of learning management system

Abstract: PurposeThis paper aims to explore the perspectives of university students on the learning management system (LMS) and determine factors that influence user experience and the outcomes of e-learning.Design/methodology/approachThis paper employs a mixed-method approach. For qualitative data, 20 semi-structure interviews were conducted. Moreover, for quantitative data, a short survey was developed and distributed among the potential respondents.FindingsThe results showed that students, particularly in programs wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 43 publications
(61 reference statements)
0
23
0
1
Order By: Relevance
“…Previous research (e.g., [28]) indicated the user experience is determinal in both the students' engagement with LMSs and their perception of online learning. Moreover, Maslov et al [29] reported that user experience could influence the students' performance. Considering the students' results in previous experiments, we can state with a certain level of confidence that the user experience is not critically low in case of the presented platform.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research (e.g., [28]) indicated the user experience is determinal in both the students' engagement with LMSs and their perception of online learning. Moreover, Maslov et al [29] reported that user experience could influence the students' performance. Considering the students' results in previous experiments, we can state with a certain level of confidence that the user experience is not critically low in case of the presented platform.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature numerous studies has been made in investigating the successful of LMS implementation from either the learner or the instructor's perspectives (Chaw and Tang, 2018;Susano and Khasanah 2022;Dhawan, 2020, Rodzi et.al., 2020. In addition, there are also studies on the usability and user experience (UX) of interacting with LMS platform (Maslov et. al., 2021;Maslov and Nikou, 2020;Nakamura et.…”
Section: Introductionmentioning
confidence: 99%
“…By investigating the UX, the results were foreseen could benefits to the UFuture designer and developer for further enhancement. This is because the success of an online learning or e-learning depend not only on the learner's perception towards the e-learning but also the quality, reliability, and usefulness of the overall e-learning platform (Maslov et. al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have recommended LMS features pertinent to learning and assessment standards as set forth by SN-Dikti [1][8] [9]. The LMS, principally, has several features ranging from uploading and downloading materials in varied formats [10], lesson plan [11], learning management [12], administrative-based management such as attendance reporting and data backup [13], recording [14], class organization [15], assignment distribution [10], assessment [16], to parent supervision [17].…”
Section: Introductionmentioning
confidence: 99%
“…This research also added validity by experts to the results of the formulation of features which are expected to increase the validity of recommended features [1]. This research aims to formulate and recommend features of LMS relevant to the SN-Dikti and fitting the need of blended learning and to implement recommended features based on Moodle version 3.10, selected as a media of implementation of feature recommendation due to the plug-in feature available [12][13] [27].…”
mentioning
confidence: 99%